St. Vincent and the Grenadines : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 2000)
As a reflection of the vulnerability to external shocks and the importance of large projects, gross domestic product growth has showed significant variations in the second half of the 1990s. The large public sector investments that have started in 1997 included the Leeward Highway, a new ferry and cruise ship berth, a banana irrigation project, and investments in health and education. During the second half of the 1990s, agriculture output declined-with output in 1999 about 20 percent lower than in 1995.